Neuroscience : fundamentals for rehabilitation - Lundy-Ekman, Laurie; Weyer, Andy (St. Louis : Elsevier, 2022)
"This sixth edition of Neuroscience: Fundamentals for Rehabilitation reflects updated concepts and recent research to present carefully selected, clinically important information essential for understanding the neurologic disorders encountered by therapists"--